The Design and Evaluation of a Large-Scale Real-Walking Locomotion Interface - Peck, T. C.; Fuchs, H.; Whitton, M. C. (IEEE transactions on visualization and computer graphics, 2012)
Redirected Free Exploration with Distractors (RFEDs) is a large-scale real-walking locomotion interface developed to enable people to walk freely in Virtual Environments (VEs) that are larger than the tracked space in their facility. This paper describes the RFED system in detail and reports on a user study that evaluated RFED by comparing it to Walking-in-Place (WIP) and Joystick (JS) interfaces. The RFED system is composed of two major components, redirection and distractors. This paper discusses design challenges, implementation details, and lessons learned during the development of two working RFED systems. The evaluation study examined the effect of the locomotion interface on users' cognitive performance on navigation and wayfinding measures. The results suggest that participants using RFED were significantly better at navigating and wayfinding through virtual mazes than participants using walking-in-place and joystick interfaces. Participants traveled shorter distances, made fewer wrong turns, pointed to hidden targets more accurately and more quickly, and were able to place and label targets on maps more accurately, and more accurately estimate the virtual environment size.